Compare and contrast peer effects on the cooperative behavior of UP Diliman students - Cabanit, Joyce Dianne D. (School of Economics, University of the Philippines Diliman, 2019)
Peer effects can be seen as the influence of interpersonal comparisons on an individual's behavior. This paper adopts the experimental design and models of Thoni and Gachter (2014) in testing for the existence and direction of peer effects in the cooperative behavior of students from the University of the Philippines Diliman campus. The present paper's results show that peer effects do exist, as was proven in the previous Thoni and Gachter (2014) paper although minimal but explainable inconsistencies with the previous results emerge as well. Additionally, the effects socioeconomic factors on cooperative behavior is also tested in this paper. Results show significant effects of gender, annual family income, and religion on prosocial behavior.